PRE-INSTITUTIONAL EDUCATION IN SERBS - Ilić, Mile; Mihajlović, Tatjana (Sinteze - časopis za pedagoške nauke , književnost i kulturu, 2016)
This paper deals with the early literacy and identifies basic specificities of pre-institutional education in ancient Slavs. Moral education plays a central role among components of educational process, namely, moral virtues are handed down from generation to generation, while intellectual education boils down to learning speech, and later to understanding of quantities, through measuring, counting and calculation. The intensity of social factors influencing the upbringing of the Slavs varies. Dominant roles are played by family, religion, as well as culture, customs and tradition. In addition, there are geographical factors, especially those relating to the climate, natural specificities and geographical territory where the Slavs settled. Conversion to Christianity represents one of the most significant civilising events in the history of the Slavic peoples. It is pronouncedly processual in nature. Little is known about the first phase of Christianiztion of the Slavs; however, cultural heritage of Christianity is significant, especially in terms of the appearance of the first Slavic alphabet. Historical sources do not present sufficient evidence that the Slavs had their own script prior to conversion to Christianity. They probably used the tally and other mnemotechnic or magic signs before they became familiar with scripts of better developed civilizations. The serious task of the creation of the first Slavic alphabet fell upon brothers Cyril and Methodius, who created the Glagolitsa, later Cyrillic. The educational work of Cyril and Methodius had an enormous importance for the future cultural development of the Slavic peoples. Cyril and Methodius’ disciples, most notably, Clement and Naum taught reading and writing in their school, in addition to providing elementary knowledge and upbringing. They taught by example, as well as through oral and written word.Thanks to the first educators and the early institutional education and upbringing, Ohrid became the centre of intense missionary work, educating the clergy from Slavic ranks. Subdeacons, deacons and presbyters prepared here were sent not only to the southwestern regions of Macedonia, but further on among the Serbs.